Structural insights into the EthR–DNA interaction using native mass spectrometry. Issue 25 (13th March 2017) - Shiu-Hin Chan, Daniel; Seetoh, Wei-Guang; McConnell, Brendan N.; Matak-Vinković, Dijana; Thomas, Sherine E.; Mendes, Vitor; Blaszczyk, Michal; Coyne, Anthony G.; Blundell, Tom L.; Abell, Chris
Abstract : The interaction between Mycobacterium tuberculosis EthR and its operator DNA has been studied by native mass spectrometry, revealing an interesting stoichiometry. Abstract : EthR is a transcriptional repressor that increases Mycobacterium tuberculosis resistance to ethionamide. In this study, the EthR–DNA interaction has been investigated by native electrospray-ionization mass spectrometry for the first time. The results show that up to six subunits of EthR are able to bind to its operator.